Needle knife papillotomy: how safe and how effective? - Dowsett, J F (1990)
Between January 1986 and July 1988 needle knife papillotomy was attempted in 103 patients after failure of conventional access for endoscopic sphincterotomy (96 cases) or diagnostic cholangiography (seven cases). Access was obtained at the same session in 36 cases and at a subsequent attempt within 2 to 5 days in a further 43, an overall success rate of 77%. The procedure related morbidity and mortality in the therapeutic group were 5.2% and 2.0% respectively. There were no deaths or complications in the diagnostic group. Needle knife papillotomy is a valuable adjunct to conventional techniques of biliary access.